HOYA DECIPULAE (APOCYNACEAE, ASCLEPIADOIDEAE), A NEW SPECIES FROM SUMATRA - Rahayu, Sri; Astuti, Inggit Puji (Research Center for Biology, 2019)
RAHAYU, S. & ASTUTI, I. P. 2018. Hoya decipulae (Apocynaceae, Asclepiadoideae), a new species from Sumatra, Indonesia. Reinwardtia 18(1): 61‒67. ‒‒ The new Hoya species from Sumatra, Hoya decipulae S.Rahayu & Astuti is here described and illustrated. It is an epiphytic shrub, thin-leaved with white flowers, similar to those of H. papaschonii Rodda, but differs in corolla and corona form. Its corolla has a unique characteristic of forming a “cage” before fully opening, as a result of the attachment of the five corolla tips which are free at the centre. The corona does not have interstaminal lobes as in Hoya papaschonii. Its corona resembles that of H. multiflora Blume and H. irisae Ferreras, Kloppenburg & Tandang from the centre to the tip but differs at the base.